(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The intricate interplay between IP law and competition law in the US, EU, and India is the subject of this research. It delves into the ways in which various legal frameworks promote innovation and, at times, clash in their efforts to keep market competition fair. To show how each nation strikes a compromise between IP protection and antitrust concerns, the study examines important laws, case law, and regulatory procedures. The interaction of copyright and digital markets, standard-essential patents, and patent licencing are some of the topics that receive special attention. While the study’s three areas share a common goal of fostering innovation and improving consumer satisfaction, they use quite different approaches and prioritise very different things. It comes to the conclusion that these legal frameworks must be continuously fine-tuned to accommodate new difficulties in fields such as platform economies, data security, and artificial intelligence as a result of globalisation and continuing technological improvements. The results add to the ongoing discussion about how to balance intellectual property and competition laws in a world where economies are becoming more interdependent.